2021
DOI: 10.1016/j.ijnonlinmec.2020.103558
|View full text |Cite
|
Sign up to set email alerts
|

Combining nonlinear vibration absorbers and the Acoustic Black Hole for passive broadband flexural vibration mitigation

Abstract: The Acoustic Black Hole (ABH) effect refers to a special vibration damping technique adapted to thin-walled structures such as beams or plates. It usually consists of a local decrease of the structure thickness profile, associated to a thin viscoelastic coating placed in the area of minimum thickness. It has been shown that such structural design acts as an efficient vibration damper in the high frequency range, but not at low frequencies. This paper investigates how different types of vibration absorbers, lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 58 publications
(90 reference statements)
1
18
0
Order By: Relevance
“…Note that either in the single and two-contact configurations, mode 4 is also attenuated, as the location of the involved impactors do not correspond to a node of mode 4. These observations agree very well with the numerical findings reported in [19,21] showing the good predictive capacity of the previously published model. In order to shed more light on the energy transfer and the related peak reduction brought by the VI-ABH, a noise excitation restricted to a low frequency range [5,400] Hz is now considered.…”
Section: Attenuation Of Low Frequency Peaks In Forced Regimesupporting
confidence: 92%
See 1 more Smart Citation
“…Note that either in the single and two-contact configurations, mode 4 is also attenuated, as the location of the involved impactors do not correspond to a node of mode 4. These observations agree very well with the numerical findings reported in [19,21] showing the good predictive capacity of the previously published model. In order to shed more light on the energy transfer and the related peak reduction brought by the VI-ABH, a noise excitation restricted to a low frequency range [5,400] Hz is now considered.…”
Section: Attenuation Of Low Frequency Peaks In Forced Regimesupporting
confidence: 92%
“…Other designs involving additional linear and/or nonlinear secondary absorber to control the lowfrequency modes have also been numerically studied in [21].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the optimization of m nes will be further studied in next section. It is clearly found that ''k nes = 1e9'' brings the best efficiency, and the same trend can be found in the linear ABH beam with a NES in (Li et al, 2021). However, it should be noted that the implementation of essential nonlinear stiffness in practical engineering is a hot topic, which is out of the scope of this paper.…”
Section: Parameters Analysis Of the Nesmentioning
confidence: 56%
“…With m nes = 0:005 and c nes = 0:5, Figure 7(b) shows the NES efficiency with k nes in the range of ½1e3, 1e12.Note that because the NES efficiency of the case k nes = 1e12 is very low, we do not plot it in this figure. It is clearly found that ''k nes = 1e9'' brings the best efficiency, and the same trend can be found in the linear ABH beam with a NES in(Li et al, 2021). However, it should be noted that the implementation of essential nonlinear stiffness in practical engineering is a hot topic, which is out of the scope of this paper.…”
mentioning
confidence: 56%
“…On the other hand, contact nonlinearity brings about immediate energy transfer, so that very effective improvements have been reported for beam ABH in [29]. The combination of added linear and nonlinear dampers to an ABH beam is studied in [30], showing also important improvements toward broadband vibration mitigation. In related fields, other studies considered similar ideas and reported results, see for example the quadratic hysteretic nonlinearity characteristic of micro-inhomogeneous materials investigated in [31] for diminishing the wave speed, or the tuned mass-loaded membranes as vibro-impact attachments on a baseline structure in [32].…”
Section: Introductionmentioning
confidence: 99%